Menin Upregulates FOXO1 Protein Stability by Repressing Skp2-Mediated Degradation in β Cells. Issue 2 (February 2019) - Jiang, Zongzhe; Xing, Bowen; Feng, Zijie; Ma, Jian; Ma, Xiaosong; Hua, Xianxin
Abstract : Objectives: Menin, a chromatin binding protein, interacts with various epigenetic regulators to regulate gene transcription, whereas forkhead box protein O1 (FOXO1) is a transcription factor that can be regulated by multiple signaling pathways. Both menin and FOXO1 are crucial regulators of β-cell function and metabolism; however, whether or how they interplay to regulate β cells is not clear. Methods: To examine whether menin affects expression of FOXO1, we ectopically expressed menin complementary DNA and small hairpin RNA targeting menin via a retroviral vector in INS-1 cells. Western blotting was used to analyze protein levels. Results: Our current work shows that menin increases the expression of FOXO1. Menin stabilizes FOXO1 protein level in INS-1 cells, as shown by increased half-life of FOXO1 by menin expression. Moreover, menin represses ubiquitination of FOXO1 protein and AKT phosphorylation, We found that menin stabilizes FOXO1 by repressing FOXO1 degradation mediated by S-phase kinase-associated protein 2 (Skp2), an E3 ubiquitin ligase, promoting caspase 3 activation and apoptosis. Conclusions: Because FOXO1 upregulates the menin gene transcription, our findings unravel a crucial menin and FOXO1 interplay, with menin and FOXO1 upregulating their expression reciprocally, forming a positive feedback loop to sustain menin and FOXO1 expression. Abstract : Supplemental digital content is available in the text.